Cyber reconnaissance surveillance and defense - Shimonski, Robert (Syngress, 2015)
Shimonski shows you how to carry out advanced IT surveillance and reconnaissance, describes when and how these techniques are used, and provides a full legal background for each threat. This book describes many new and leading-edge surveillance, information-gathering, and personal exploitation threats taking place today, including Web cam breaches, home privacy systems, physical and logical tracking, phone tracking, picture metadata, physical device tracking and geo-location, social media security, identity theft, social engineering, sniffing, and more. Real-world examples are examined using key concepts from cases in the news around the world. --